Mortality in Cardiogenic Shock Patients Is Predicted by Pao2/Fio2 (Horowitz Index) Measured on ICU After Venoarterial Extracorporeal Membrane Oxygenation Implantation. (24th September 2021) - Scherer, Clemens; Lüsebrink, Enzo; Joskowiak, Dominik; Feuchtgruber, Vanessa; Petzold, Tobias; Hausleiter, Jörg; Peterss, Sven; Massberg, Steffen; Hagl, Christian; Orban, Martin
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Venoarterial extracorporeal membrane oxygenation treatment in patients with severe cardiogenic shock can cause or aggravate acute lung injury. In our retrospective analysis, we aimed at identifying markers for acute lung injury after arrival on ICU, which predict mortality of those patients. DESIGN: Observational, monocentric, retrospective analysis. SETTING: Cardiac ICU of Ludwig Maximilian University Hospital, Munich, Germany. PATIENTS: Two-hundred eleven patients undergoing venoarterial extracorporeal membrane oxygenation treatment for severe cardiogenic shock were included into this analysis. Patients who died within 24 hours after venoarterial extracorporeal membrane oxygenation implantation were excluded. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: To determine lung injury, we investigated the influence of Pao2/Fio2 ratio (Horowitz index). The lowest Horowitz index was measured on ICU 6–12 hours after venoarterial extracorporeal membrane oxygenation implantation. An optimal cutoff value of less than 126 for Horowitz index to predict mortality was identified via receiver operating characteristic analysis (area under the curve, 0.62). Patients with Horowitz index less than 126 had a 30-day mortality rate of 67.5% compared to 37.5% with a Horowitz index greater than or equal to 126 ( p < 0.001). Multivariate analysis identified Horowitz index less than 126 as an independent risk factor of ICU mortality (odds ratio, 3.6; 95% CI, 1.8–7.3; p < 0.001). CONCLUSIONS: In this hypothesis-generating analysis, a Horowitz index less than 126 is associated with increased mortality in patients with cardiogenic shock and venoarterial extracorporeal membrane oxygenation, which may serve as a threshold for further therapeutic interventions.